2019 6th International Conference on Control, Decision and Information Technologies (CoDIT) 2019
DOI: 10.1109/codit.2019.8820303
|View full text |Cite
|
Sign up to set email alerts
|

Data Pre-processing Techniques in the Regional Emission's Load Profiles Case

Abstract: Different data sources, data types and platforms are involved in modelling emissions load profiles. In our case, we model emission load profiles at the regional or city level. However, we found missing values, redundancy and inconsistency in the datasets, and in most cases data preprocessing is unavoidable. Data pre-processing converts the data into a clean and tidy dataset for the subsequent modelling steps or statistical analyses. Therefore, some common techniques for data pre-processing such as cleaning, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…In data collection and pre-processing phases, it is important to study the latter comprehensively, as it can improve data quality and the accuracy of the result [52]. Data corruption, missing values and outliers are the commonest problems in data-processing [52,53]. In general, there are four tasks in data pre-processing: cleaning, transformation, integration and reduction [52,54,55].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In data collection and pre-processing phases, it is important to study the latter comprehensively, as it can improve data quality and the accuracy of the result [52]. Data corruption, missing values and outliers are the commonest problems in data-processing [52,53]. In general, there are four tasks in data pre-processing: cleaning, transformation, integration and reduction [52,54,55].…”
Section: Methodsmentioning
confidence: 99%
“…Data corruption, missing values and outliers are the commonest problems in data-processing [52,53]. In general, there are four tasks in data pre-processing: cleaning, transformation, integration and reduction [52,54,55]. Table 2 summarises the common problems of data pre-processing tasks and their solutions:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence, load-shifting forms part of our research on DSM in the residential sector (Figure 1). In our previous works on synthesising residential electricity load profiles [28,[35][36][37], we found that appliances are mainly used to synthesize domestic load profiles. In accordance with what was revealed in [15], there is a need to incorporate the consumption patterns of electrical appliances into DSM models.…”
Section: Introductionmentioning
confidence: 99%